2007
DOI: 10.1167/iovs.06-1104
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sutureless Transplantation of Bioadhesive-Coated, Freeze-Dried Amniotic Membrane for Ocular Surface Reconstruction

Abstract: The FCFD-AM retained most of the biological characteristics of FD-AM. Consequently, this sutureless method of transplantation of FCFD-AM is safe, simple, and useful for ocular surface reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Sekiyama et al performed sutureless AMT with fibrin glue for ocular reconstruction of rabbit eyes [91]. They prepared a freezedried (FD) AM that was coated with fibrin glue (Tisseel).…”
Section: Amtmentioning
confidence: 99%
“…Sekiyama et al performed sutureless AMT with fibrin glue for ocular reconstruction of rabbit eyes [91]. They prepared a freezedried (FD) AM that was coated with fibrin glue (Tisseel).…”
Section: Amtmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, the outcomes of AMT using fibrin glue for corneal ulceration, perforation, and ocular surface reconstruction have been reported in clinical and experimental studies. [9][10][11][12][13] However, the results of pterygium surgery with AMT using fibrin tissue sealants have been evaluated in limited number of studies. Pfister and Sommers 14 were the first to report the use of fibrin glue for amniotic membrane grafting in two patients with primary and in one with recurrent pterygium.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were essentially corroborated in another study (Sekiyama et al, 2007). The fibrin bioadhesive biodegrades within 2 weeks, whereas the amniotic membrane persists for at least 12 weeks, providing sufficient time for epithelialization (Sekiyama et al, 2007). Sutureless transplantation with fibrin glue or ProKera™ is reportedly a safe and easy method that avoids complications related to sutures and shortens the time of surgery (Kheirkhah et al, 2006).…”
Section: Human Amniotic Membrane Transplantationmentioning
confidence: 62%
“…The authors found that suture fixation tends to promote membrane contraction, raised membrane edges, and epithelial ingrowth into the submembrane space (Szurman et al, 2006). These findings were essentially corroborated in another study (Sekiyama et al, 2007). The fibrin bioadhesive biodegrades within 2 weeks, whereas the amniotic membrane persists for at least 12 weeks, providing sufficient time for epithelialization (Sekiyama et al, 2007).…”
Section: Human Amniotic Membrane Transplantationmentioning
confidence: 72%